1
$\begingroup$

I have the following system of differential equations:

$$ \begin{align*} \dot x &= -2y\\ \dot y x-\dot x y &= 1+y^2 \end{align*} $$

with the usual initial conditions $x(0)=x_0$ and $y(0)=y_0$. I don't know how to solve that, but when I plug it into Mathematica, it manages to give me an answer in terms of elementary functions. One of the solutions is:

$$ \begin{align*} x(t) &= \frac{t^2 y_0^4-2 t^2 y_0^2+t^2+2 t x_0 \left(y_0^2-1\right) y_0+x_0^2 y_0^2-x_0^2}{x_0 \left(y_0^2-1\right)} \\ y(t) &= \sqrt{\frac{t^2 y_0^4-2 t^2 y_0^2+t^2+2 t x_0 \left(y_0^2-1\right) y_0+x_0^2 y_0^2}{x_0^2}} \end{align*} $$

I don't believe Mathematica has access to black voodoo magic, so what's the trick here?

$\endgroup$
4
$\begingroup$

Plug first equation value of $\dot x $ into second and separate the variables

$$ \int \frac{dy}{1-y^2} = \frac{dx}{x} $$

which can be solved in terms of elementary functions.

EDIT1:

The above treats $ \dot y = \dfrac {dy}{dx} $. But treating as $t$ time independent variable $ \dot y=y′(x) \dot x, $ it becomes :

$$ \int \frac{2\, y\,dy}{y^2-1} = \int \frac{dx}{x} $$

as suggested by mickep below.

$\endgroup$
  • $\begingroup$ I think you forgot that it is $\dot y=\frac{dy}{dt}$ in the left-hand side of the second equation, and not $y'(x)$. Using the chain rule, one can of course write $\dot y=y'(x)\dot x$. Then, the differential equation becomes $$\frac{2y}{y^2-1}\,dy=\frac{1}{x}\,dx.$$ $\endgroup$ – mickep Oct 20 '15 at 16:02
  • $\begingroup$ Yes thanks, that was a hint which basically can tackle $y$, shall convert to answer. $\endgroup$ – Narasimham Oct 21 '15 at 1:18

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.